Nobody left behind? Equity and the drivers of stunting reduction in Vietnamese ethnic minority populations - Harris, Jody; Huynh, Phuong; Nguyen, Hoa T.; Hoang, Nga; Tran, Lan Mai; Tuyen, Le Danh; Nguyen, Phuong Hong (Springer, 2021)
Vietnam has successfully reduced population stunting, but ethnic minority groups are being systematically left behind, limiting progress on national reductions. This mixed methods study aims to understand how drivers of stunting reduction differ between ethnic majority and minority communities. We used decomposition analysis to explain key determinants of stunting change between 2000 and 2010; and framework analysis to qualitatively assess changes in policy, actors and narratives that have underpinned these over decades. Our analysis shows that stunting reductions are associated with increased household wealth (accounting for 61% of change), improved access to specific health services (16%), and changes in level of maternal education (12%). Despite multiple actors involved in change and a large set of policies designed to address inequities, many among Vietnam’s defined ethnic minority groups are not finding themselves able to effectively engage with central government plans for their communities, and central policies often do not consider their preferences or limitations. This in turn impacts the nutrition of minority groups through the determinants above. Vietnam has achieved the easier portion of stunting reduction through national economic growth and sustained commitment to socially-oriented policy. In order to tackle the remaining pockets of high malnutrition, more attention, thought and funding will need to focus on marginalised ethnic minority communities. The current national development discourse aims to incorporate minorities into mainstream majority systems. This paper argues that should rather take into account their particular needs and preferences to address and overcome the identified determinants of malnutrition.